Using taxes to reform health insurance : pitfalls and promises - Aaron, Henry J.; Burman, Leonard (Brookings Institution Press, 2008)
"Examines the role that taxes currently play, the likely effects of recently introduced health savings accounts, the challenges of administering major subsidies for health insurance through the tax system, and options for using the tax system to expand health insurance coverage"--Provided by publisher